(untitled) (diségno, 2018)
Over time, the scope of Survey had periods of greater or lesser consideration, but I would also say of mere attention of academic and non-academic scholars who confronted in the field of Drawing. This is due to the wide spectrum of cultural interests that are present in this sphere: from the geometry to the project, from the techniques to the systems. The considered focuses have an enormous variety of scale, from the object to the landscape.